Daphnane diterpenoid orthoesters with an odd-numbered aliphatic side chain from Daphne pedunculata - Tan, Lingjian; Otsuki, Kouharu; Kikuchi, Takashi; Zhou, Di; Li, Ning; Huang, Li; Chen, Chin-Ho; Li, Wei (Journal of natural medicines, 2024)
Daphnane diterpenoids were recognized for their extensive range of potent biological activities. In the present study, phytochemical investigation including LC–MS/MS analysis resulted in the identification of five daphnane diterpenoid orthoesters ( 1 – 5 ). Among the five daphnane diterpenoids, two previously unreported compounds, daphnepedunins I and J ( 2 and 4 ) were isolated from Daphne pedunculata . The structure of new compounds was elucidated with extensive physicochemical and spectroscopic analyses. Their structure was characterized by the presence of an unusual odd-numbered aliphatic chain connected to an orthoester. The isolated compounds were evaluated for their anti-HIV activity against HIV-1 infection of MT4 cells, and the results indicated that compound 1 showed the most potent anti-HIV activity with an IC 50 value of 0.82 nM. Graphical Abstract